A Pathological Mini-Atlas of Microbiologically Influenced Corrosion and Deterioration (MIC / MID) Cases - Javaherdashti, Reza (Foundations of Materials Science and Engineering, 2022)
"A Pathological Mini-Atlas of Microbiologically Influenced Corrosion and Deterioration (MIC/MID) cases", authored and edited by Dr. Reza Javaherdashti, is a book that, in collaboration with several international world-known MIC professionals, has been written to shed light on some areas of MIC/MID that are still in the dark as well as designing a new systematic insight into the study of MIC/MID phenomena. Anti-Microbial Coating, Biofilm, Cathodic Depolarisation Theory (CDT), Corrosion System, Corrosion Risk, Corrosion Modelling, Culture Independent Methods, Culture Dependent Methods, External Electron Transfer (EET), EMIC (Electrical MIC), Exopolymer Substances (EPS), Encapsulation, Antifouling, Bottom-Of-The Line (BOL), Black Mould, Biocide (Oxidising, Non-Oxidising/Organic), Disbonded or Damaged Coatings, Fuzzy Calculus, Fick's Second Law, Flagella, Fouling, Gliding and Twitching, Hydrophilicity, Hydrophobicity, Iron Reducing Bacteria (IRB), Pipeline Inspection Gauges (PIG), Key Performance Indicator (KPI), Microbiologically Influenced Corrosion (MIC), Microbiologically Influenced Deterioration (MID), Microbial Corrosion, Planktonic Bacteria, Root Cause Analysis, Re-Growth, Sulphate Reducing Bacteria (SRB), Stress Corrosion Cracking (SCC), Microbial Succession, Sessile Bacteria, Solid Phase Dwelling (SPD) Bacteria, Sulphur Oxidising Bacteria (SOB), Sulphureta, Symbiosis, Syntrophy, Temenos, TRIZ, Tubercle, Volatile Organic Compounds Levels (VOC), Wetting Materials Science, Mechanical Engineering, Mechanics.